Systematic tendencies in scene viewing - Benjamin W. Tatler; Benjamin T. Vincent (Bern Open Publishing, 2008)
While many current models of scene perception debate the relative roles of low- and highlevel factors in eye guidance, systematic tendencies in how the eyes move may be informative. We consider how each saccade and fixation is influenced by that which preceded or followed it, during free inspection of images of natural scenes. We find evidence to suggest periods of localized scanning separated by 'global' relocations to new regions of the scene. We also find evidence to support the existence of small amplitude 'corrective' saccades in natural image viewing. Our data reveal statistical dependencies between successive eye movements, which may be informative in furthering our understanding of eye guidance.